Restoration of the historical masonry structures based on laboratory experiments. (September 2016) - Bozkurt, Tarik Serhat; Sayin, Baris; Akcay, Cemil; Yildizlar, Baris; Karacay, Nese
Abstract: In historical structures, restoration applications have become necessary because their life cycle of structural and non-structural members is completed due to natural result of material structure, environmental conditions and user errors. In this study conducted in this respect, conventional and modern techniques which is conserve the historical building's identity were adopted by referring to opinions of expert consultants and academicians within architecture and civil engineering fields. The first stage of the study contains; i. Specify of material characteristics, ii. Determination of mixture ratios using physical and chemical tests conducted on samples taken from the building, iii. Preparation of original material mixtures using the obtained data. In the second stage, architectural implementations were determined based on lab test results. Within the scope of architectural implementations, featureless additions that do not comply with the original materials of the building, floor/ceiling tiling and wall plasters were removed; masonry members on facades and floors were completed, repaired and cleaned; doors and windows were renovated; stairs and safety rails were returned to their original condition. Finally, a survey was carried out to determine whether the restoration was effective and to evaluate the building's relationship with urban environment, its aura and universal originality as well as its originality of material, form and function. It is concluded that the developed historical building restoration process is suitable as a practical tool in the historical building restoration studies for the prediction of accurate restoration applications. Highlights: The consolidation process of the examined structure is performed considering historical identity. Featureless additions in the examined building have been removed. The laboratory tests have been carried out in order to determine intervention decisions regarding the examined building. Research survey has been fulfilled to evaluate restoration applications.